Adapting a coach-assisted web-based intervention for parents of adolescents who refuse school: qualitative study with users of the Partners in Parenting Plus programme - Anna Smout; Glenn Melvin; Anthony Jorm; Marie B. H. Yap (BJPsych Open, 2024)
Background School refusal is a heterogenous problem which typically emerges in adolescence and co-occurs with internalising disorders. A substantial proportion of adolescents do not respond to existing treatment modalities; thus, novel, effective intervention options are needed. Partners in Parenting Plus (PiP+) is a coach-assisted, web-based intervention designed to empower parents to respond to adolescent internalising disorders.